Navigating the athlete role: identity construction within New Zealand`s elite sport environment - Ryan, C. (Journal of Quantitative Analysis in Sports, 2018)
The purpose of this study was to explore how involvement within New Zealand`s elite athlete development programme - athlete carding - has impacted the identity construction of this elite athlete population. Semi-structured interviews were conducted with a purposeful sample of 17 carded athletes from 8 different sports, followed by inductive thematic analysis of emerging key themes. In order to ensure that participants` voices were accounted for throughout the data representation process, athlete`s individual stories were collated into collective accounts and represented using direct quotes. The potential for participants to become engulfed within the athlete role was evident throughout each of the carded athletes` stories. In many cases this role was consolidated through expectations on athletes` time and energies, as well as external scrutiny and performance pressures resulting from their involvement within the carding system. Whilst many athletes appeared to passively accept an increasing emphasis being placed upon their athlete role identity, some seasoned participants questioned why the carding system encouraged this solitary existence at the expense of a more multi-dimensional sense of self. Results suggest that the carded athlete system it is not currently meeting its potential to develop world class `holistic` athletes. As such, it is important that High Performance Sport New Zealand re-examines its policy of performance-based funding and engages in a wide-reaching education programme which promotes the importance of athletes developing a well-balanced sense of self alongside their sporting potential.